Fractionation and charaterization of rambutan seed fats (Nephelium Lappaceum L.) and their potential applications as cocoa butter improver - Azzatul Fatonah Salim (2020)
Rambutan ( Nephelium lappaceum L.) is a commercial tropical crop which is appreciated by consumers because of its pleasant aroma, refreshing flavor, and exotic appearance. Rambutan seeds are the main by-products in the canning industry and has attracted attention for their feasibility in industrial applications. In this study, rambutan seed fat (RSF) was fractionated by two-stage acetone fracti.onation and their physicochemical, thermal properties (melting and crystallization) and morphology of RSF fractions were determined in order to identify their potential applications. The results showed that the second solid fraction (FrS) exhibited the highest SMP (49.03 °C) and lowest IV (27.57 g iodine/g).The major fatty acids in all solid fractions were stearic (15.1-21.6%), oleic (25.0-35.5%), and arachidic (42.7-46.9%) acids. The high-melting symmetrical monounsaturated triacylglycerols (Hm-SMT) of FrS which is the sum of SOS (3.82%) and POS (1.19%) were also found to be higher than first solid fraction (F1-S). The SFC of FrS at 20 °C (78.57%) and 35 °C (22.95%) were found to be higher than Fi-5, indicating a harder solid fraction. The melting onset (26.92-31.24 °C) and offset (49.57- 52.84 °C) temperatures for both F1-S and FrS increased from the crude RSF and shifted towards higher temperatures. F2-S showed the densely packed microstructure compared to that of crude RSF and F1-S with the diameter of 20-30 μm under microscopic observation. This study revealed that by performing fractionation of RSF, a cocoa butter improvers (CBI) could be prepared by blending them with other fats that has the potential to be utilized in food industry.